Analysis of The Impact of Bone Sugar Factory Waste Water On Quality of Teko River Water - Zulfikar Efendy, Andi; Farid Samawi, Muhammad; Maming, Maming (Devotion : Journal of Research and Community Service, 2022)
The Bone sugar factory discharges its liquid waste into the Teko River water body. The Teko River is widely used for agricultural and fishery purposes, so it is necessary to maintain the quality of the water to suit its designation. Liquid waste from the Bone sugar factory can affect the water quality of the Teko River. The purpose of this study was to determine the water quality status of the Teko River due to the discharge of waste water from the Bone sugar factory. Observations were made on the water body of the Teko River from the up stream and down stream of the disposal of sugar factory wastewater at 3 stations. Station 1 is the point before the discharge of wastewater, station 2 is the point of discharge of wastewater and station 3 is the point after discharge of wastewater, the recipient of the impact. The results of the research conducted on the Teko river water body showed that the status of water quality at station 1 was the category of lightly polluted, station 2 was in the category of lightly polluted and station 3 was in the category of meeting quality standards. Determination of water quality using the Pollution Index method according to Minister of Environment Decree Number 115 of 2003 using class II river water quality standards according to Government Regulation Number 22 of 2021quality standards according to Government Regulation Number 22 of 2021.